Analisis Penerapan Tax Planning Dalam Rangka Mencapai Efisiensi Pajak Pertambahan Nilai (PPN) Pada PT. Kusuma Sampurna Mulia - Adelya Zahraeni (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2022)
Tax is a burden that can result in smaller company profits. Companies with taxes as a burden, of course, need careful planning in order to achieve tax cost efficiency. As in PT. KSM has several things that are less efficient related to the payment of Value Added Tax (VAT) which is too large. In order to achieve tax efficiency on the payment of Value Added Tax (VAT) payable by PT. KSM needs to make tax planning efforts (tax planning). The purpose of this study is to analyze tax planning or tax planning that can be done in order to achieve efficiency in the payment of Value Added Tax (VAT) payable. The research method used in this research is descriptive qualitative analysis method. The results of this study indicate that with the company making all purchases to Taxable Entrepreneurs , the company can make the cost of Value Added Tax (VAT) more efficient, reaching Rp. 132,443,612. Before the tax planning was carried out, the tax burden was Rp. 258,940,738 and became Rp. 126,497,126 after the tax planning was carried out.